'To Aleppo gone ...' (Oxford)
viii, 234 sayfa
Keywords: “To Aleppo Gone... is a festschrift offered in honour of Jonathan Tubb, former Levant curator and Keeper of the Department of the Middle East at the British Museum. It includes 44 contributions invited from Jonathan's friends and colleagues from across the world, with each short essay exploring a single idea and its wider ramifications. The assembled volume also reflects the development of Jonathan's own career and professional interests, with a focus on the Jordan Valley and southern Levant, but also extending to north Syria, Mesopotamia, the protection of endangered cultural heritage, and the lives of early archaeological pioneers.” --